Realist evaluation cases of the uptake and use of citizen science tools for water quality management: Vaal-Triangle public primary schools teachers and Mpophomeni enviro-champs - Madiba, Morakane Stephinah (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
This study employs a theory-based approach to evaluate citizen science (CS) interventions in two distinct cases: the Mpophomeni enviro-champs and the Vaal-Triangle primary school teachers. These interventions were designed to foster social learning, enhance education or participants' understanding of water quality impacts, and promote community or public participation for improved water management. GroundTruth, a multidisciplinary consulting company with expertise in water resources and environmental engineering, collaborated as partners in these CS projects. Utilizing qualitative realist evaluation theory, the study delves into the intricate context-mechanismoutcome (CMO) configurations for each case, seeking depth insight into the outcomes of these citizen science initiatives. Data collection involved interviews, document analysis, and participant observations to construct a comprehensive understanding of the interventions' impact. In the case of the Vaal-Triangle primary school teachers, the CS intervention yielded positive results, significantly influencing teaching practices and instilling shared values for sustainable water quality management in both classrooms and the surrounding communities. However, the study revealed the need for continued evaluation and comprehensive dialogue among stakeholders, including teachers, school governing bodies, local municipalities, the Department of Basic Education, and the broader community to ensure the effectiveness, sustainability, and transformative potential of these interventions. In contrast, the Mpophomeni enviro-champs experienced a different set of outcomes. The CS intervention catalyzed numerous opportunities for the volunteers, forging a collaborative relationship between citizens and the government. Despite their socio-ecological vulnerability, these volunteers exhibited remarkable resilience and willingness to contribute, calling for formalization mechanisms such as remuneration and skill recognition to sustain and enhance their participation. This study provides insights into citizen science interventions, foregrounding volunteerism as a means of fostering fair and inclusive participation. It emphasizes the significance of combining social and classroom learning in achieving sustainable water quality management objectives. Furthermore, the research highlights the pivotal role of informed citizenship, which necessitates an understanding not only of environmental activism but also of effective political engagement to influence decision-making processes effectively. By challenging historical barriers and revealing new perspectives, this study offers a reflective thinking tool to advance transformative policy development in South Africa and beyond, promoting informed and responsible public participation in water quality management and fostering the sustainability of precious water resources.
Keywords: Realist evaluation; Citizen science; Water quality management -- South Africa Vaal Triangle; Social learning; Voluntarism; Ubuntu (Philosophy)